Breast Cancer Estrogen Receptor Status According to Biological Generation: US Black and White Women Born 1915–1979. Issue 5 (20th September 2017) - Krieger, Nancy; Jahn, Jaquelyn L; Waterman, Pamela D; Chen, Jarvis T
Abstract: Evidence suggests that contemporary population distributions of estrogen-receptor (ER) status among breast cancer patients may be shaped by earlier major societal events, such as the 1965 abolition of legal racial discrimination in the United States (state and local "Jim Crow" laws) and the Great Famine in China (1959–1961). We analyzed changes in ER status in relation to Jim Crow birthplace among the 46, 417 black and 339, 830 white US-born, non-Hispanic women in the Surveillance, Epidemiology, and End Results (SEER) 13 Registry Group who were born between 1915 and 1979 and diagnosed (ages 25–84 years, inclusive) during 1992–2012. We grouped the cases according to birth cohort and quantified the rate of change using the haldane (which scales change in relation to biological generation). The percentage of ER-positive cases rose according to birth cohort (1915–1919 to 1975–1979) only among women diagnosed before age 55. Changes according to biological generation were greater among black women than among white women, and among black women, they were greatest among those born in Jim Crow (versus non–Jim Crow) states, with this group being the only group to exhibit high haldane values (>|0.3|, indicating high rate of change). Our study's analytical approach and findings underscore the need to consider history and societal context when analyzing ER status among breast cancer patients and racial/ethnic inequities in its distribution.